Albuminuria within the Normal Range Can Predict All-Cause Mortality and Cardiovascular Mortality. Issue 1 (27th January 2022) - Kang, Minjung; Kwon, Soie; Lee, Jeonghwan; Shin, Jung-Im; Kim, Yong Chul; Park, Jae Yoon; Bae, Eunjin; Kim, Eun Young; Kim, Dong Ki; Lim, Chun Soo; Lee, Jung Pyo
Key Points: Despite interest in low-grade albuminuria and poor clinical outcomes, evidence from a large-scale population is lacking. In this large cohort study, low-grade albuminuria was associated with all-cause and cardiovascular mortality. In the general population, low-grade albuminuria should be carefully monitored. Visual Abstract: Abstract : Background: Despite interest in low-grade albuminuria and poor clinical outcomes, evidence from a large-scale population is lacking. Therefore, we identified the association of low-grade albuminuria within the normal range with all-cause and cardiovascular (CV) mortality. Methods: After excluding individuals with urine albumin-creatinine ratio (ACR) ≥30 mg/g ( n =6094), this cohort study analyzed 43, 396 adults who participated in the National Health and Nutrition Examination Survey (1999–2016). Participants were divided into four quartiles of ACR. The primary outcome was all-cause mortality, and the secondary outcome was CV mortality. Multivariable Cox proportional hazards models were used. Results: During a median 7.9 years of follow-up, 3516 (9%) participants died. Compared with the reference group (Q1, ACR <4.171 mg/g), low-grade albuminuria groups were associated with all-cause mortality (Q3, ACR ≥6.211 to <10.010 mg/g, hazard ratio [HR], 1.25 [95% CI, 1.11 to 1.41]; Q4, ACR ≥10.010 mg/g, HR, 1.57 [95% CI, 1.41 to 1.76]) in a multivariable hazards model. A similar pattern was also seen in the association of low-grade albuminuria with CV mortality. Subgroup analyses showed that low-grade albuminuria was also associated with all-cause mortality in the nondiabetic group, nonhypertensive group, and non-CKD group (eGFR ≥60 ml/min per 1.73 m 2 ). Conclusions: Our findings suggest that low-grade albuminuria is associated with all-cause and CV mortality. Low-grade albuminuria should be monitored, even for patients with low CV risk.